Association Between Postoperative Thrombocytopenia and Outcomes After Coronary Artery Bypass Grafting Surgery - Li, Jinghang; Yu, Dongmin; Song, Yuanyuan; Cheang, Iokfai; Wang, Xiaowei (Frontiers in Surgery, 2021)
OBJECTIVES: The effect of postoperative thrombocytopenia on adverse events among coronary artery bypass graft (CABG) patients remains unclear. This study aims to investigate the association between postoperative thrombocytopenia and perioperative outcomes of CABG. METHODS: This is a retrospective study with MIMIC-III (Medical Information Mart for Intensive Care III) database. Adult patients who underwent CABG were included to analyze the impact of thrombocytopenia in patients’ outcomes. Postoperative thrombocytopenia was defined as a platelet count <100× 109/L on the first day after CABG surgery. A multivariable logistic regression analysis was utilized to adjust the effect of thrombocytopenia on outcomes for baseline and covariates, and to determine the association with outcomes. RESULTS: A total of 4,915 patients were included, and postoperative thrombocytopenia occurred in 696 (14.2%) patients. Postoperative thrombocytopenia was not associated with increased 28-day mortality (OR 0.75; 95% CI 0.33-1.72; P=0.496) or in-hospital mortality (OR 0.75; 95% CI 0.34-1.63; P=0.463) after adjusting for confounders. Regarding the secondary outcomes, it was associated with a higher risk of a prolonged stay in the intensive care unit (OR 1.53; 95% CI 1.18-1.97; P=0.001), prolonged hospital stays (OR 1.58; 95% CI 1.21-2.06; P=0.001), prolonged mechanical ventilation time (OR 1.67; 95% CI 1.14-2.44; P=0.009), and a trend toward increased occurrence of massive bleeding (OR 1.41; 95% CI 1.00-2.01; P=0.054). There was no significant association between an increased risk of prolonged vasopressor use and the continuous renal replacement therapy rate. CONCLUSIONS: Postoperative thrombocytopenia was associated with prolonged ICU and hospital stays but not with increased perioperative mortality among CABG patients.